PINK1 is activated by mitochondrial membrane potential depolarization and stimulates Parkin E3 ligase activity by phosphorylating Serine 65. Issue 5 (May 2012) - Kondapalli, Chandana; Kazlauskaite, Agne; Zhang, Ning; Woodroof, Helen I.; Campbell, David G.; Gourlay, Robert; Burchell, Lynn; Walden, Helen; Macartney, Thomas J.; Deak, Maria; Knebel, Axel; Alessi, Dario R.; et al.
Summary: Missense mutations in PTEN-induced kinase 1 (PINK1) cause autosomal-recessive inherited Parkinson's disease (PD). We have exploited our recent discovery that recombinant insect PINK1 is catalytically active to test whether PINK1 directly phosphorylates 15 proteins encoded by PD-associated genes as well as proteins reported to bind PINK1. We have discovered that insect PINK1 efficiently phosphorylates only one of these proteins, namely the E3 ligase Parkin. We have mapped the phosphorylation site to a highly conserved residue within the Ubl domain of Parkin at Ser 65 . We show that human PINK1 is specifically activated by mitochondrial membrane potential (Δψm) depolarization, enabling it to phosphorylate Parkin at Ser 65 . We further show that phosphorylation of Parkin at Ser 65 leads to marked activation of its E3 ligase activity that is prevented by mutation of Ser 65 or inactivation of PINK1. We provide evidence that once activated, PINK1 autophosphorylates at several residues, including Thr 257, which is accompanied by an electrophoretic mobility band-shift. These results provide the first evidence that PINK1 is activated following Δψm depolarization and suggest that PINK1 directly phosphorylates and activates Parkin. Our findings indicate that monitoring phosphorylation of Parkin at Ser 65 and/or PINK1 at Thr 257 represent the first biomarkers for examining activity of the PINK1-Parkin signalling pathway in vivo . Our findings also suggest that small molecule activators of Parkin that mimic the effect of PINK1 phosphorylation may confer therapeutic benefit for PD.